(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The study compares the effects of chemical inactivation conditions using formalin and β-propiolactone on the avian influenza virus subtype A/H5. The aim of the study was to identify conditions that ensure complete inactivation of the virus-containing suspension while preserving antigenic activity, using formalin at final concentrations of 0,05 % and 0,1 %, and β-propiolactone at final concentrations of 0,025 % and 0,05 %. The optimal conditions for the studied virus-containing suspension were: 0,05 % formalin for 16 hours at 37 ± 0,5 °C, and 0,025 % β-propiolactone for 4 hours at 4 ± 0,5 °C. In experiments on chicks, it was found that the virus-containing suspension inactivated under optimal conditions induced an increase in titers of specific antibodies. The results demonstrate the possibility of optimizing the inactivation process, taking into account the different sensitivities of virus strains to inactivating agents, for the development of effective vaccines against avian influenza.